1995
DOI: 10.1046/j.1525-1438.1995.05010045.x
|View full text |Cite
|
Sign up to set email alerts
|

Infection by human papillomavirus types 6, 11, 16, 18, 31, 33 and 35 of the cervix in Japanese women

Abstract: Exfoliated cervical cells from 321 Japanese women were examined for human papillomavirus (HPV) DNA types 6, 11, 16, 18, 31, 33 and 35 using polymerase chain reaction (PCR) and dot-blot hybridization methods. HPV DNA was present in 9.3% of patients with normal cervixes, 72.7% of patients with cervical intraepithelial neoplasia (CIN) and 77.8% of patients with invasive carcinoma. Younger patients (/=50 years) had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
(10 reference statements)
2
4
1
Order By: Relevance
“…However, the second most common types in the current study were HPV‐18 and HPV‐58 (11.4%), and HPV‐31 and HPV‐45 were not detected in patients with carcinoma. The prevalence of HPV‐16 in patients with HSIL in the current study (51.9%) was comparable to its prevalence in other previous reports (43–72%) that used the PCR method 13–15. The next most common types in this study differed slightly from those reported in other studies.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, the second most common types in the current study were HPV‐18 and HPV‐58 (11.4%), and HPV‐31 and HPV‐45 were not detected in patients with carcinoma. The prevalence of HPV‐16 in patients with HSIL in the current study (51.9%) was comparable to its prevalence in other previous reports (43–72%) that used the PCR method 13–15. The next most common types in this study differed slightly from those reported in other studies.…”
Section: Discussionsupporting
confidence: 82%
“…The prevalence of HPV-16 in patients with HSIL in the current study (51.9%) was comparable to its prevalence in other previous reports (43-72%) that used the PCR method. [13][14][15] The next most common types in this study differed slightly from those reported in other studies. HPV-58, in addition to HPV-18, was the second most common type, whereas HPV-31 and HPV-35 were more frequent in other studies.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…In particular, the prevalence of HPV types 6 and 11 were 3% and 15%, respectively. In Japan, HPV types 6, 11, 16, 18, 31, 33 and 35 were present in 9.3% of women with normal cervixes 2 …”
Section: Discussionmentioning
confidence: 99%
“…In Japan, HPV types 6, 11, 16, 18, 31, 33 and 35 were present in 9.3% of women with normal cervixes. 2 While the high prevalence of genital HPV in women is reported, there is little known regarding the prevalence in men. International Agency for Research on Cancer (IARC) investigators reported a high prevalence (3.5% -39.0%) of genital HPV in the penile skin of healthy men.…”
Section: Discussionmentioning
confidence: 99%